Natives and Newcomers: Canada's "Heroic Age" reconsidered - Trigger, Bruce Graham (McGill-Queen's University Press, 1994)
Plusieurs réimpressions
Keywords: Autochtones; Français; Iroquoiens; Iroquois

Les Indiens, la fourrure et les Blancs - Trigger, Bruce Graham (Boréal et Seuil, 1992)
Keywords: Autochtones; Fourrure; Français

Montreal Canoes and their Cargoes - White, Bruce (Le Castor fait tout. Fifth North American Fur Trade Conference, 1985, 1987)
Keywords: Fourrure

Le commerce des fourrures à Montréal: documentation et méthodes d'analyse - Allaire, Gratien (Le Castor fait tout. Fifth North American Fur Trade Conference, 1985, 1987)
Keywords: Fourrure